Possible transmission from mother to child at covid-19 through breastfeeding (Research, Society and Development, 2021)
With the high and fast spread of the covid-19 in the population, some worries has been raised, like the safety of pregnant women and that are in breastfeeding. This attention is about the possible transmission from mother to son through breast milk. Objective: verify the possibility of a possible transmission from mother to son through breast milk. Methods: the articles searches were done at the electronics databases SciELO, PubMed and Lilacs. For the articles searches were used selected descriptors through consultations to the DECS (subjects descriptors in health science of BIREME), being them "breastfeeding", "breast milk" and "covid-19", the search in the literature was in the last three years. Results: when performing the screening using the inclusion criteria, there is for study a total of eight articles, where 50% of these articles showed negative samples of SARS-CoV-2 in the breast milk, whilst the others 50% recognize the SARS-CoV-2 presents in at least one sample of breast milk. Conclusion: the studies covered in this review showed that breastfeeding is not considered a vertical transmission medium for the coronavirus.